Construction and validation of educational technology for family members of people with venous ulcers - Saionara Leal Ferreira; Islene Victor Barbosa; Solange Gurgel Alexandre; Rita Neuma Dantas Cavalcante de Abreu; Cecília Freitas de Araújo Mota; Jennifer Ferreira Figueiredo Cabral; Geise Moreira Sales de Oliveira; Cybelly Teixeira Vidal (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To build and validate an educational technology in the form of a booklet, aimed at the family members of people with venous ulcers to assist them in their care. Methods: A methodological study, which went through the stages of bibliographic survey and situational diagnosis for the construction of the booklet and validation of content, appearance, and adequacy with judges and the target audience. The Content Validity Index, the Suitability Assessment of Materials, and the Concordance Index were used. Results: In the validation with the content and appearance judges, the booklet showed an excellent overall Content Validity Index (tCVI=0.92). The technical judges evaluated the booklet as "superior" (average of 91%). The booklet underwent adjustments, and validation was performed with the target population, reaching an agreement rate higher than 75%. Conclusion: The educational booklet developed was validated for content and appearance and considered suitable for use by family members of people with venous ulcers.